Pengaruh Kualitas Kehidupan Kerja dan Budaya Organisasi Terhadap Kepuasan Kerja Karyawan Pada CV Amanah Pinang Ranti - Yanthi Meitry Gunawan; Atik Atikah; Iwan Setiawan Rofiq (JUDICIOUS, 2021)
This study aims to determine the effect of the quality of work life (quality of work life) and organizational culture on employee job satisfaction. This study uses a non-probability sampling technique on saturated sampling, so that the total population and sample are combined into one as many as 70 people. The analytical technique used is multiple linear regression analysis using SPSS software version 25. The results of the study at a significance level of 5% indicate that: (1) the quality of work life has a positive and significant effect on employee job satisfaction, as evidenced by the value of tcount > ttable (7.456 > 1.995) with a significance value of 0.000 which is smaller than 0.05 (0.000 < 0.05), (2) organizational culture has a positive and significant effect on employee job satisfaction, as evidenced by the value of tcount > ttable (7.272 > 1,995) with a significance value of 0.000 which is smaller than 0.05 (0.000 < 0.05) and (3) the quality of work life and organizational culture together have a positive and significant effect on employee job satisfaction, as evidenced by the result of Fcount > Ftable (45,093 > 3.16) with a significance value of 0.000 which is smaller than 0.05 (0.000 < 0.05) quality of work life ) and organizational culture by influencing employee job satisfaction 57.4% while the remaining 43.6% is influenced by other factors that are not included in the research model. With multiple regression equation value Y=3.060 + 0.406 X1 + 0.475 X2 + e.